Incision size changes after cataract surgery with intraocular lens implantation: comparison of 2 preloaded IOL implantation injectors. Issue 2 (February 2020) - Haldipurkar, Suhas S.; Shetty, Vijay; Haldipurkar, Tanvi; Dhamankar, Rita; Sehdev, Nancy; Khatib, Zain; Nagvekar, Pranoti; Mhatre, Paresh; Setia, Maninder Singh
Abstract : A comparison of UltraSert and Vivinex intraocular lens delivery systems found no difference in changes in the incision size, visual acuity, and surgically induced astigmatism in cataract surgery. Abstract : Purpose: To compare incision size enlargement at different times of cataract surgery and visual outcomes after surgery in 2 different intraocular lens (IOL) delivery systems (Vivinex iSert and UltraSert Preloaded IOL Delivery System). Setting: Tertiary care eye institution. Design: Prospective nonrandomized comparison study. Methods: All eyes had uneventful temporal clear corneal phacoemulsification cataract surgery. The surgery was done by standard direct horizontal chop with a bimanual irrigation aspiration of the cortex. The primary incision size was measured after clear corneal incision, after the completion of phacoemulsification, and after IOL implantation. Results: The study comprised 276 eyes of 220 patients. The mean initial corneal incision was similar in both groups (2.2 mm). There was no significant difference in the mean incision size after phacoemulsification between the 2 groups (2.250 mm ± 0.068 mm [SD] vs 2.251 ± 0.066 mm [SD], P > .99). There was no significant difference in the mean (SD) incision size after IOL insertion between the 2 groups (2.367 ± 0.066 mm vs 2.369 ± 0.062 mm [SD], P = .815. The corrected distance visual acuity was 6/6 at 1 month in 80% of the participants in the UltraSert group and 86% in the Vivinex group. After adjusting for age, sex, grade of cataract, and IOL power, no significant difference was found in the magnitude of surgically induced astigmatism (SIA) in the Vivinex group compared with the UltraSert group (0.06, 95% CI, −0.11 to 0.24; P = .47). Conclusions: No significant difference was found in the change in the incision size, visual acuity, and SIA between UltraSert and Vivinex IOL delivery systems. This suggests that both IOL delivery systems are comparable in terms of post-IOL delivery incision enlargement for incisions of 2.2 mm.